Cita Rasa dan Kreativitas Aci dalam Kuliner Bandung - Hartanto, Lidiya Giovanni; Budiman, Debora Olivia; Febrina, Marshella (Ideas Publishing, 2025)
Bandung cuisine is known as an icon of West Java gastronomy with rich innovation and local flavors. Aci, as the basic ingredient of traditional snacks, symbolizes Sundanese creativity in processing simple ingredients. However, culinary modernization and the influx of fast food pose challenges such as declining consumer interest and the risk of losing local culinary identity. This study aims to examine variations of aci based snacks in Bandung and their role in maintaining traditional snack existence. The method used is descriptive qualitative through field observations and interviews. Results show that aci based snacks such as cimin and cimol preserve culture